2013
DOI: 10.5301/jbm.5000033
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Clock Genes in Patients with Colorectal Cancer

Abstract: Recent studies have demonstrated the influence of clock genes in cell cycle regulation, cell proliferation, apoptosis and DNA damage recognition and repair. There is evidence suggesting the implication of clock genes in colorectal cancer (CRC) development and progression. The aim of this study is to evaluate the expression levels of clock genes in CRC and correlate them with patients' prognosis. Forty-two CRC samples (from 24 males and 18 females), their paired noncancerous tissues and 8 biopsies from healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 22 publications
4
34
0
Order By: Relevance
“…These experimental studies suggested that Period genes control the cell cycle and act as tumour suppressors. This is consistent with the findings in this review where Period is decreased in colorectal tumours . Decreased expression of Period genes has also been reported in other types of cancer such as breast cancer , endometrial carcinoma , non‐small‐cell lung cancer , acute myeloid leukaemia , gliomas and hepatocellular carcinoma .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These experimental studies suggested that Period genes control the cell cycle and act as tumour suppressors. This is consistent with the findings in this review where Period is decreased in colorectal tumours . Decreased expression of Period genes has also been reported in other types of cancer such as breast cancer , endometrial carcinoma , non‐small‐cell lung cancer , acute myeloid leukaemia , gliomas and hepatocellular carcinoma .…”
Section: Discussionsupporting
confidence: 92%
“…Bmal1 was examined in five studies . It was found to be significantly decreased in one study and significantly increased in two .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pro-proliferative effect of certain clock genes was not specific to untransformed cells, since very similar properties were also attributed to cancer cell lines. For instance, human colorectal cancers often show higher expression of Clock or Bmal1 genes compared to healthy tissue [112,113,114]. In agreement with this, overexpression of CLOCK increases proliferation of colorectal carcinoma cells in vitro and in vivo [115].…”
Section: Does the Circadian Clock Support Tumorigenesis?mentioning
confidence: 88%
“…It has been shown that the PER1 , PER2 , PER3 and Dec1 genes are expressed in a similar circadian manner in human peripheral blood mononuclear cells, with the peak level occurring during the habitual time of activity [35] suggesting that the oscillation of PER3 may also be an essential factor in maintaining circadian rhythm. Besides, altered PER3 expression has been reported in various cancers, including CML [19,20], HNSCC [21], HCC [18], and CRC [36]. Further investigations of PER3 function may reveal the direct links between deregulation of PER3 and prognosis in GC patients.…”
Section: Discussionmentioning
confidence: 99%